Thermophysical and optimization of performance and emission of turbocharged si engine using gasoline, ethanol and fusel oil blends - Mohd Rosdi, Salleh (2021)
Recently, the use of renewable fuels as substitute of fossil fuel in gasoline engine is increased significantly. Moreover, the use of fossil fuel for energy conversion produces exhaust gases that lead to air pollution. Ethanol is a well-known source of alternative fuel, however, fusel oil which is one of the by-products have also become one of the potential energy resources. It is waste product after ethanol process. An objective of the study is to investigate the engine performance, exhaust emission, combustion quality and combustion stability in the engine cylinder using gasoline, ethanol and fusel oil blends. Then all data of fuel blends were analyse using Response Surface Methodology (RSM) to optimize result for engine testing. The experiment was conducted on a commercial four-cylinder turbocharged gasoline engine. The gasoline fuel and blends with ethanol and fusel oil physicochemical properties were measured. This includes density, air-fuel ratio, heating value and viscosity. The results show brake power, brake thermal efficiency, exhaust gas temperature reduced dramatically when percentage of fuel blends increased by 5%, 3.8% and 4.7% respectively, compared to gasoline. The brake specific fuel consumption significantly increases when fuel blends increased by 5% compared to gasoline. Meanwhile, the NOx, HC and CO emission show improvements when used fuel blends by 13%, 3.4% and 11.5% respectively, compared to gasoline. The in-cylinder pressure shows correlation as cylinder temperature, rate of heat release, rate of pressure rise and mass fraction burn. They were significantly reduced by 3.7%, 2%, 3.7% and 2% respectively, compared to gasoline. Although the engine stability showed a significant increase of the coefficient of variation by 2.16%, 2.20%, 2.36%, 2.46%, 2.5%, 2.8% for F10, F20, F30, E10, E20, E30 respectively. Coefficient of variation for mean effective pressure using gasoline is 2.03%. While coefficient of variation of fuel blends increase such as E10, E20, E30 F10, F20 and F30 by 2.16%, 2.20%, 2.36%, 2.46%, 2.5% and 2.8% respectively. Optimization using RSM was showed the model was significant at 3000 rpm, 40% engine throttle and using fusel oil 30%. In addition, the R-squared was close to 1 and desirability was 0.833%. As a conclusion, although fusel oil is considered a by-product of ethanol production, it has comparable performance with gasoline and ethanol itself.